The Evaluation Of The Door To Door Collection Program For Motor Vehicle Tax Arrears In Banten Province During The Covid-19 Pandemic - Iwan Hermawan; Rita Myrna; Heru Nurasa; Nina Karlina (Universitas Padjadjaran, 2022)
Tax revenue from the Motor Vehicle Tax sector in Banten Province continues to increase from year to year and is the dominant sector of local revenue. This revenue should still be optimized because there are still many arrears or delays in paying motor vehicle taxes, especially in 2020 there is a COVID-19 pandemic which has an impact on people's purchasing power, including the purchase of motorized vehicles and payment of motor vehicle tax (PKB) as well as on The SAMSAT service sector was closed and restricted. After all, it was affected by the COVID-19 prevention program through the Governor of Banten Decree Number 443/Kep.114-Huk/2020 concerning the Determination of the Extraordinary Events of Corona Disease 2019 (COVID-19) in the Banten Province. Thus, a special program is needed to collect these arrears, for this reason, this study will discuss in more depth the evaluation of the door to door collection program for motor vehicle tax arrears in Banten Province during the COVID-19 pandemic using the CIIP evaluation model from Stufflebeam including context evaluation, input evaluation, process evaluation and product evaluation. This study uses a descriptive qualitative approach. Collecting data in this study using interviews, observations and documents.